(untitled) (Nóema, 2020)
Following P. F. Strawson’s distinction between descriptive and revisionary metaphysics in this essay, I examine these two different approaches to an ontology of events and argue that a revisionary approach based on modern physics is a more reliable basis to construct an ontological theory. Descriptive metaphysics, in accordance with Aristotle and Kant, gives priority to the role that events play in ordinary language. Events turn out to be dependent on substances since they are all activities of material bodies. Revisionary metaphysics, in accordance with Whitehead, Russell and Quine, rejects ordinary language as a guide to ontology. Events, in this approach, are the primary entities and material bodies turn out to be relatively monotonous patterns in event sequences. This is the conclusion from Einstein’s theory of relativity and from various interpretations of quantum mechanics. Science has outgrown the substance theory of Aristotle and his followers.